Safety in anesthesiology during the pandemic due to the new SARS-CoV-2 coronavirus - Amy Torres Montes de Oca (Centro Provincial de Información de Ciencias Médicas, 2021)
Safety in anesthesiology can be defined as the risk reduction from the unnecessary damage associated with the anesthetic care to an acceptable minimum, taking into account the existing knowledge, the available resources and the context where the medical care of this specialty is presented. To such effects, the security measures that should be taken in the perioperative period are described, that were elaborated taking the international recommendations on the topic in question as a starting point, which are of great utility due to the speed with which this pandemic has expanded.